Nurturing Student Autonomy: the role of Self-determination theory in Academic coaching - Lubennikova E. V. (Coaching psychology: methodology, theory, practice, 2025)
the article explores the pivotal role of Self-Determination Theory in fostering student autonomy and well-being with the help of academic coaching. As educational paradigms shift towards learner-centered approaches, the development of interventions that promote intrinsic motivation and self-directed learning becomes increasingly critical. This study investigates how the core tenets of SDT – autonomy, competence, and relatedness – can be effectively integrated into academic coaching practices to enhance student engagement and academic performance. The article highlights successful coaching strategies, practical insights and psychometric scales that can enhance self-awareness and empower students to take ownership of their learning.
Keywords: академический коучинг; теория самодетерминации; поддержка студенческой автономии; self-determination theory; student autonomy support; academic coaching